EVALUASI PEMANFAATAN RUANG DI KAWASAN PESISIR KABUPATEN HALMAHERA UTARA BERDASARKAN RENCANA ZONASI WILAYAH PESISIR DAN PULAU-PULAU KECIL - Nehemia Tirajoh; Sonny Tilaar; Suryono (SPASIAL, 2023)
From the perspective of economic interests as an agropolitan region, Dimembe Subdistrict is a part of North Minahasa district's provincial strategic area (KSP). According to field observations made in the Dimembe District, there hasn't been any infrastructural development so far. The Agropolitan Area in the Dimembe Subdistrict still has low service levels for its agricultural infrastructure, which leads to underutilization and inefficient production and delivery of agricultural goods. This study's goal was to locate and assess the infrastructure needed to enable the growth of agropolitan regions in North Minahasa regency's Dimembe district. Descriptive qualitative and quantitative research approaches were employed in this study. According to the study's findings, there is generally excellent infrastructure accessible in rural areas for initiatives to expand agricultural areas in the Dimembe District. The study, which is based on the Public Works Service's regulatory criteria, received a score of 69.8%, indicating that there is enough rural infrastructure to sustain the agricultural industry. Keyword: Evaluation, Availability of Infrastructure, Development of Agricultural Areas, Dimembe District